A community-based study of hypertension and cardio-metabolic syndrome in semi-urban and rural communities in Nigeria - Onodugo Obinna D; Ijoma Chinwuba K; Ulasi Ifeoma I (BMC, 2010)
Abstract Background The prevalence of cardio-metabolic syndrome (CMS) is increasing worldwide. In people of African descent, there is higher prevalence of hypertension and complications than other races. Bearing in mind these facts, we looked at the CMS in the general population and the population with hypertension. Using the new International Diabetes Federation (IDF) definitions of CMS, we studied its prevalence in semi-urban and rural communities in South-east Nigeria in relation to hypertension. Method This is a cross sectional population based study involving 1458 adults aged from 25 to 64 years. Diagnosis of CMS was based on the new IDF criteria using the anthropometric measurements for Europids as there is none yet for blacks. Hypertension was defined according to the WHO/ISH criteria. Results The overall prevalence of CMS was 18.0% in the semi-urban community as against 10.0% in the rural community increasing to 34.7% and 24.7% respectively in the population with hypertension. The prevalence of co-morbidities - hyperglycaemia, abdominal obesity, and hypertriglceridaemia were 13.9%, 41.1% and 23.9% while in the hypertensive populations they were 21.2%, 55.0% and 31.3% in the general population in both communities combined. Except for low HDL cholesterol, every other co-morbidity was higher in hypertensive population than the general population. Conclusion The high prevalence of CMS in the semi-urban population especially for the population with hypertension underscores the double burden of disease in developing countries. The lesson is while infections and infestations are being tackled in these countries the non-communicable diseases should not be neglected.